1865 The identification of de-novo pathogenic genetic mutations in adolescent patients with ADHD. (15th December 2022) - Kamal, Madeeha; Fakhro, Khalid; Hashem, Sheema; Haris, Muhammad; Alassaf, Anood
Abstract : Objectives: This study analyses a sample of adolescents in Qatar with attention deficit disorder, to find associated pathogenic genetic mutations using whole genome sequencing. Methods: A sample of 14 families of adolescents with ADHD was investigated in this study. The total number of participants was 84 people. That included affected patients with ADHD and their parents. Some of the patients' healthy siblings were included for comparison. The patients attended the adolescent medicine clinic in Sidra hospital, Doha. The age group of the participant patients was between 12 and 18 years, the majority of them were males, and apart from ADHD, they were healthy with no underlying neurological diseases. They were diagnosed with ADHD by consultants in adolescents' medicine based on their clinical presentation and DSM-5 criteria, 1 supported by their scores in the Vanderbilt questionnaire, which was filled by their parents and teachers. Whole blood samples from the participants were sent for genetic study using whole exome sequencing (WES). Results of these tests were carefully studied for genetic mutations, and compared with their parents' results to check whether these mutations were inherited from one or both parents or occurred sporadically. Results: This study has identified pathogenic de-novo variants in 5 genes ( HERC2, FARP2, GRIA2, SMURF1, and TUBB3 ), in 5 probands out of 14 families (table 1). These genes are expressed in the brain, and they have clear associations with some neurological conditions. The HERC2 gene mutation is associated with autism spectrum disorder in childhood, the FARP2 is associated with Brachydactyly-Mental Retardation syndrome, the GRIA2 is associated with Psychiatric and Neurodevelopmental Disorders, the SMURF1 is associated with Speech-Language disorder and the TUBB3 is associated with cortical dysplasia with other complex brain malformations. Conclusions: Attention-deficit hyperactivity disorder (ADHD) is a common childhood-onset neurodevelopmental disorder characterized by inattention, impulsivity, and hyperactivity. ADHD exhibits substantial heritability, with rare monogenic variants contributing to its pathogenesis. ADHD prevalence in Qatar is considered significantly high, with almost 10% of the Qatari children suffering from ADHD. 2 This could be linked to the fact that the rate of consanguinity amongst the Qatari population is particularly high reaching up to 54%. 3 This study has found five de novo genetic mutations in five families of patients with ADHD, supporting the evidence of the genetic basis of ADHD. Identifying these mutations will contribute to the future of precision medicine, which will allow doctors around the world to tailor their management based on their patient's unique genetic characteristics, for accurate diagnosis and optimum care. References: Narad ME, et al . Parent-teacher agreement on ADHD symptoms across development. Bradshaw LG. Prevalence of ADHD in Qatari School-Age Children. J Atten Disord . Ben-Omran T, et al . Effects of consanguinity in a cohort of subjects with certain genetic disorders in Qatar. Mol Genet Genomic Med .